Ethical Context of Organization and Turnover Intention of Women Employees: The Mediating Role of Perceived Organizational Support - Ganji, Seyedeh Fatemeh Ghasempour; Johnson, Lester W; Banejad, Babak; Sorkhan, Vahid Babazadeh (Journal of Social Economics Research, 2020)
Previous studies found that females understand and react to behavioral factors such as ethical behaviors and organizational support different from men. As females appear to have higher senility to ethics and supportive behaviors, thus, their behavioral response including turnover intention (TI) has been gaining a vast amount of attention in literature. This study aims to examine the influence of ethical context on female employees’ turnover intentions. It also examines the mediating effect of perceived organizational support. The sample of 210 was obtained from female employees at Ferdowsi University of Mashhad, Iran using a standard questionnaire. We employ Partial Least Square Structure Acquisition Modeling (PLS-SEM) to analyze data. The results of the research demonstrate that perceived organizational support is a mediator in the link between ethical context and turnover intention. The negative direct and indirect effects of ethical context on turnover intention were also supported. Moreover, perceived organizational support negatively effect of turnover intention.